COMPARISON BETWEEN PHYSICAL CONDITIONING STATUS AND IMPROVEMENT IN ARTISTIC GYMNASTS AND NON-ATHLETES PEERS - Vassilis Mellos; George Dallas; Paschalis Kirialanis; Giovanni Fiorilli; Alessandra Di Cagno (Science of Gymnastics Journal)
The aim of the present study was to evaluate the status and improvement of physical conditioning in male gymnasts, aged 9-12 years, and to compare these results with non-athletes. Fifty seven gymnasts, with an experience of 4-5 years in training and competition and 74 non-athletes of the same age were enrolled in the study. All participants were tested twice, in a 12 month interval, on 9 depended variables selected from the Euro Fit Test Battery. Results showed that gymnasts had better results than non-athletes in overall the tests (p<0.01). Except the improvement in the throwing tests, which seems to be mostly age related, the significant improvement in the jumping tests, was more evident in the gymnasts (p<0.01), whereas the improvement in the flexed arm hang and balance tests were observed in the athlete group only. The 30m running speed improvement was observed only in the non- athlete group. Neither group displayed any improvement in the push-ups and the sit-and-reach tests. In conclusion, the status and improvement of physical conditioning in pre-adolescence is significantly related to the kind and extend of physical activity performed and the scholastic motor activity curriculum should be implemented with arm strength conditioning, balance and flexibility programs.